After the 'need for ... a father': 'the welfare of the child' and 'supportive parenting' in assisted conception clinics in the UK. (23rd March 2017) - Lee, Ellie; Sheldon, Sally; Macvarish, Jan
Abstract : The law governing assisted conception in the United Kingdom (UK) (the Human Fertilisation and Embryology Act 1990) mandates through section 13(5) that clinicians make 'child welfare' assessments before proceeding with treatment. In the 1990 Act, section 13(5) stated that assessment should take into account 'the need … for a father', but in section 13(5) of a revised Human Fertilisation and Embryology Act in 2008 the words 'a father' were replaced with 'supportive parenting' in order to signal official recognition of same-sex parents. This article challenges the idea that this might be seen as an unequivocally progressive development through reference to a growing body of scholarship that critically evaluates the attention that policy makers have come to pay to 'parenting'. It discusses the sociopolitical context that gave rise to section 13(5) and the pressures that led to its reform. Findings from an interview study with members of staff who work in assisted conception clinics in the UK are then discussed, focusing on staff's perceptions of the new policy, the meanings they ascribe to the term 'supportive parenting' and their opinions about the responsibility they are given under law for child welfare. The article concludes that professionals' understandings of their role resonate strongly with the wider realities of the oversight of parent–child relations considered characteristic of policies on parenting.